Kandungan Flavonoid dan Aktivitas Antibakteri Ekstrak Etanol Daun Sintrong (Crassocephalum crepidiodes) Terhadap Bakteri Bacillus cereus - Rose Simanungkalit, Elia; Selamet Duniaji, Agus; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 2 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i02.p10, 2020)
The aim of this research was to determine the content of flavonoid and antibacterial activity of ethanol extract of sintrong leaf (Crassocephalum crepidiodes) on Bacillus cereus. This research used a Completely Randomized Design (CRD) with treatment concentrations extract which were 20%, 40%, 60%, 80%, and 100% with three replications and resulting in 15 experimental units. Data were presented with tables and pictures and analyzed in descriptive statistic. Ethanol extract of sintrong leaf contained flavonoid compounds of 1,75% and was able to inhibit the growth of Bacillus cereus at a concentration of 20% with an average 12,3 mm and strong inhibition categories, also has a bacteriostatic character with percentage range death of Bacillus cereus 80,9% - 93,7%. Keywords : flavonoid, sintrong leaf, antibacterial, bacillus cereus.